Pengembangan Kebijakan Siak Kabupaten Hijau Melalui Pemberdayaan Masyarakat Berbasis Kampung Hijau - Marta, Auradian; Hasanuddin, Hasanuddin; Wicaksono, Baskoro; Tinov, Tiyas; Asrida, Wan; Ishak, Ishak; Febrina, Rury; Ferlan, Margina; Essio Mento, Meris (Civiliza Publishing, 2025)
The community service is based on a policy innovation issued by the Siak District Government in 2018 related to Siak Green District. In general, the Green Siak policy is encouraged to harmonies efforts to save and protect the environment with the economic benefits of natural resource management, which still considers aspects of environmental sustainability through the Ecological Fiscal Transfer (EFT) approach. The method of Community Service is carried out by brainstorming, group discussions, simulations and effective facilitation. The results of Community Service include: (1). Measuring the implementation of the Siak Hijau District policy and government programmed in community development, especially based on green villages. (2) Increasing the capacity of village governance towards village independence and village community welfare within the framework of the Siak Hijau District policy. (3) Mapping the potential and challenges of the village in improving environmental performance according to the indicators of Siak Hijau District. (4) Improving village local economic development through entrepreneurship, tourism, and culture through BUMKam. (5) Improving the quality of environmental health, especially in waste management and generating innovation through strengthening the Kampung Waste Bank institution.